Optimizing Local Own-Source Revenue through PBB-P2: A Tax Justice and Good Governance Analysis within the Framework of Regional Autonomy and Fiscal Decentralization - Ratu Eha Salhah; Rotua Valentina Sagala (Golden Ratio of Law and Social Policy Review, 2026)
This article examines two questions: first, what constitutional and statutory basis authorizes local governments to optimize the Rural and Urban Land and Building Tax (PBB-P2) as an instrument of Locally Generated Revenue; second, how the 2025 wave of PBB-P2 rate increases across several Indonesian regions should be evaluated through the lenses of tax justice and good governance. Using a normative legal method that combines statutory, conceptual, and case-based approaches, the study draws on fiscal decentralization theory and tax justice theory. The findings show that PBB-P2 optimization rests on a sound constitutional and statutory basis. However, the public controversies in Pati, Jombang, Semarang Regency, Bone, Parepare, and Cirebon City were driven less by an absence of legal authority than by two deficits: a tax justice deficit, in which sharp tax increases were not matched by protections for taxpayers with limited ability to pay, and a governance deficit, marked by weak transparency in property valuation and limited public participation before policy changes took effect. By contrast, DKI Jakarta shows that revenue optimization and social protection can proceed together through instruments such as the non-taxable property value threshold (NJOPTKP), a tiered assessment ratio, and an annual increase cap. The study recommends periodic and transparent property valuation updates, fuller use of the fairness instruments already available under Indonesia's Regional Tax and Levy Law (Law No. 1/2022 on Fiscal Relations between the Central and Regional Governments), mandatory public consultation before major tax policy changes, and standardized procedures for objections and refunds.